FAULT TOLERANCE IMPLEMENTATION FRAMEWORK ON DOOR CONTROL SYSTEM PROTOTYPE USE PROGRAMMABLE PERIPHERAL INTERFACE (PPI)-BASED 8255 MICROSOFT VISUAL BASIC 6.0 - Martian Logi Otama; Lingga Hermanto, Skom., MMSI (Jurnal Sistem Komputer, 2006)
Fault-tolerance describes a computer system designed to handle the event when the system experienced an error (fault) the work, which the backup or replacement procedures will replace the work experience component failures without interrupting the continuity of the system. In this tool is used as an indicator of DC motors for driving the door moves prototypes. Keypad to function as provider of the input signal to drive the door. PPI 8255 serves as an interface between the PC Tools.Â